Penguatan Karakter Beriman, Bertaqwa kepada Tuhan yang Maha Esa, dan Berakhlak Mulia melalui Kegiatan HIMA Prodi PPKn - Suardi Suardi (Universitas Lambung Mangkurat, 2023)
Background: there is student behavior that is contrary to the values and norms of society. The aim of the research is to strengthen the character of the Pancasila student profile to students through HIMA study program activities. The research method is mixed methods, data collection techniques using questionnaires, observation, interviews and documentation, then analyzed qualitatively and quantitatively. The results showed that the activities of the Al Arqom dalillah Pancasila assemblies, Ramadhan safaris, religious activities, physical and mental activities, interactions without discrimination, social services and deliberation activities can shape the profile character of Pancasila students in tertiary institutions, especially on the dimension of Faith, Faith in God Almighty , and Noble Morals. The conclusion of the study is that student activities in HIMA Study Program can provide character strengthening for all students